The Influence of Price and Product Quality on Consumer Purchase Decisions for Skincare Products - Sela Novitasari; Bambang Permadi (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of price and product quality on consumer purchase decisions of skincare products. The research method used is a quantitative approach with data collection techniques through the distribution of questionnaires to respondents. The population in this study is all consumers who have bought and used skincare products, with sample determination using purposive sampling techniques. The number of samples used was 100 respondents. The data analysis techniques used include validity test, reliability test, classical assumption test, multiple linear regression analysis, partial test (t), simultaneous test (F), and determination coefficient (R²) with the help of statistical software. The results of the analysis show that price has a significant influence on the purchase decision of Skincare Products, as well as the quality o f the product which also has a significant effect. Together, price and product quality show a significant influence on purchasing decisions. A determination coefficient value (R²) of 0.995 or 99.5% indicates that the price and product quality variables are able to explain the purchase decision by 99.5%, while the remaining 0.5% is influenced by other factors not discussed in this study.